Design and optimization of a high-resolution PET detector module for small-animal PET based on a 12 × 12 silicon photomultiplier array. (6th November 2015) - Du, Junwei; Schmall, Jeffrey P; Di, Kun; Yang, Yongfeng; Judenhofer, Martin; Bec, Julien; Buckley, Steve; Jackson, Carl; Cherry, Simon R
Abstract: A high resolution PET detector module was designed and optimized based on a custom 12 × 12 Silicon photomultiplier (SiPM) array and commercially available readout electronics (SensL Ltd., Ireland). The total area of this SiPM array is 50.2 mm × 50.2 mm, and consists of 3 × 3 sections each containing 4 × 4 SiPM elements. Each SiPM, made using 35 um microcell technology, has a sensitive area of 3.0 mm × 3.0 mm in a 4.0 mm × 4.0 mm package and is fabricated into an array with 4.2 mm pitch. The performance of this detector was evaluated using 16 × 16 arrays of 0.975 mm × 0.975 mm × 12 mm polished LYSO crystals. Such small crystals make one-to-one coupling between the SiPM and LYSO crystal impractical. In this work, therefore, the detector was evaluated using light sharing approaches. Flood histogram quality, signal amplitude, and energy resolution were compared at different bias voltages (28.0–32.5 V in 0.5 V intervals) using five light guides with different thickness (from 0.8 mm to 2.0 mm) at a fixed temperature of 5 °C by coupling the LYSO array to a single SiPM section. The best flood histogram was obtained at a bias voltage of 29.5 V using the 1.0 mm thick light guide. Under these conditions, all the LYSO crystals can be clearly separated and the average energy resolution was 18.6 ± 1.9%. The timing resolution was 6.0 ± 0.1 ns after leading edge time walk correction, obtained by using two identical detectors consisting of two 12 × 12 SiPM arrays and two 16 × 16 LYSO arrays. The LYSO array was moved such that it was coupled to the center of four SiPM sections and all crystals could still be clearly resolved. These results show that a high-resolution small-animal PET scanner could be developed based on these large-area SiPM arrays and commercially available electronics.